2014
DOI: 10.1007/s11172-014-0725-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of poly(arylene ether ketones)

Abstract: The results of investigations of the synthesis and properties of poly(arylene ether ketones) prepared by electrophilic and nucleophilic substitution reactions are generalized and described systematically. Data on the effect of the polycondensation conditions on the molecular weight and properties of polymers are considered. A scientific knowledge about the effect of the synthesis conditions and the chemical structure of poly(arylene ether ketones) on their proper ties enabled the directed synthesis of polymers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…It has been previously shown that the BC method is more accurate, as it discriminates the bonds between the main chain and side groups that contribute significantly to polymer rigidity [57]. We can observe the same picture in Table 7, as follows: MAPEs and MPEs are mainly lower for BC, except for the C2 polymer.…”
Section: Predicted Gas Transport Parameterssupporting
confidence: 72%
See 2 more Smart Citations
“…It has been previously shown that the BC method is more accurate, as it discriminates the bonds between the main chain and side groups that contribute significantly to polymer rigidity [57]. We can observe the same picture in Table 7, as follows: MAPEs and MPEs are mainly lower for BC, except for the C2 polymer.…”
Section: Predicted Gas Transport Parameterssupporting
confidence: 72%
“…Polyimides have the most numerous representation (Table 1); therefore, for this class, the predicted data are closest to the experimental ones [28,31,34]. For such a practically important and extensive class of polymers as poly(arylene ether ketone)s [56,57], the database [15] contains only 41 different structures, so for this class, the verification of predicted data is very interesting. Thus, in this work, a number of poly(arylene ether ketone)s (PAEKs), as well as poly(diphenylene phthalide), which only has a common structural element with one of the PAEKs, were synthesized and studied, and the process of verifying various methods for predicting transport parameters for these polymers was carried out.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Among these methods, the method of introducing bisphenol A into the polymer structure is one of the simplest methods and has been researched at the present stage. 24,25 Bisphenol A based polyether ether ketone is an amorphous polymer with good mechanical and optical properties.…”
Section: Introductionmentioning
confidence: 99%